PENGEMBANGAN KARAKTER MULTIKULTURAL SANTRI PADA PONDOK PESANTREN SALAFIYAH DI KALIMANTAN SELATAN - Akbar, Nadzmi; Rif'at, Muhammad (Alhadharah: Jurnal Ilmu Dakwah, 2019)
At the national policy of the Republic of Indonesia in 2010-2025 to prioritize the development of national character, because the Indonesian people at this time the values start from national identity, higher, contradictory, towards people of different religions, ethnicities and cultures. To build this character, the world of education is the backbone to carry out the mission of building multicultural characters of Indonesian citizens. Salafi Islamic Boarding School or Islamic Boarding School is one of the educational institutions in Indonesia, which also has an obligation to build the multicultural character of the students. How did the Salafiyah Islamic Boarding School develop the multicultural character of the students? The research method in this research is descriptive qualitative, data collection techniques with observation, interviews and documentaries. The results of this study found that the development of multicultural character in Salafiyah Islamic boarding school in an integrated manner in the field of moral education in an integrated manner, the organizational culture of the Salafiyah Islamic boarding school could develop the multicultural character of students, leaders, chaplains and teachers help display a very important practice for guests .